Multimodal Approach on Finger Vein and Fingerprint by Using Visual Steganography for Efficient Biometric Security - Anitha, P; Grace, M (International Journal of Computer Sciences and Engineering, 2025)
Nowadays our systems need strong security to protect data and resources access from unauthorized persons. For that purpose, biometric-based authentication system provides more security than other approaches. Uni-modal biometric systems use only one biometric trait such as fingerprint, finger vein, voice, face, ear, iris, retina etc., which has some limitations due to noise, spoof attacks etc., The multimodal biometric system is the combination of more than one biometric trait to authenticate an individual. In this paper, a multimodal approach has been proposed by integrating the finger vein and fingerprint to enhance the performance of personal recognition system. Preserving the privacy of stored biometric templates in a centralized database is of more important at present. Visual Steganography provides a very powerful technique by which one secret can be distributed in two or more shares. When the shares on transparencies are superimposed exactly together, the original secret can be discovered without computer participation. In the enrollment procedure, the secret key is encrypted by using AES algorithm and by using the visual steganographic technique, the encrypted secret key is shared between the two images. The share1 is kept as the users' ID card and the share2 is stored in the database. In the verification procedure, new finger vein and fingerprint images are obtained and verified with the images stored in the database. It is computationally hard to obtain the biometric image from any individual stored sheets. This paper explores the possibility of using visual steganography for efficient biometric security in the multimodal approach.